2020
DOI: 10.3390/polym12102389
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Properties of Biodegradable Poly(Butylene Sebacate-Co-terephthalate)

Abstract: In this study, poly(butylene sebacate-co-terephthalate) (PBSeT) was successfully synthesized using various ratios of sebacic acid (Se) and dimethyl terephthalate (DMT). The synthesized PBSeT showed a high molecular weight (Mw, 88,700–154,900 g/mol) and good elastomeric properties. In particular, the PBSeT64 (6:4 sebacic acid/dimethyl terephthalate mole ratio) sample showed an elongation at break value of over 1600%. However, further increasing the DMT content decreased the elongation properties but increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
6
18
0
Order By: Relevance
“…A peak corresponding to the –CH 3 of PLA at 2945 cm −1 , 2996 cm −1 [ 38 ] and the –CH– of PLA at 2997 cm −1 (asym), 2946 cm −1 (sym), and 2881 cm −1 stretch [ 39 ]. The –CH 2 of PBSeT was appeared at 2919 cm −1 , 2851 cm −1 [ 36 ]. However, it occurred nearby each other, so whole peaks were appeared in the range 2800–3000 cm −1 as small round curves.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A peak corresponding to the –CH 3 of PLA at 2945 cm −1 , 2996 cm −1 [ 38 ] and the –CH– of PLA at 2997 cm −1 (asym), 2946 cm −1 (sym), and 2881 cm −1 stretch [ 39 ]. The –CH 2 of PBSeT was appeared at 2919 cm −1 , 2851 cm −1 [ 36 ]. However, it occurred nearby each other, so whole peaks were appeared in the range 2800–3000 cm −1 as small round curves.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 and Table 3 shows the tensile-strength characteristics and stress–strain curves of the neat PLA, control, and blend specimens prepared with various HDI contents. According to previous research results, because PBSeT showed high elongation, it was expected to remarkably affect the tensile properties of the highly brittle PLA [ 36 ]. The neat PLA and simple-blend control specimens showed tensile strengths of approximately 93 and approximately 52 MPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations